Patient-centered care in the Middle East and North African region: a systematic literature review - Reeham Ahmed Alkhaibari; Jennifer Smith-Merry; Rowena Forsyth; Gianina Marie Raymundo (BMC, 2023)
Abstract Background The need for patient centered care (PCC) and its subsequent implementation has gained policy maker attention worldwide. Despite the evidence showing the benefits and the challenges associated with practicing PCC in western countries there has been no comprehensive review of the literature on PCC practice in the Middle East and North African (MENA) region, yet there is good reason to think that the practices of PCC in these regions would be different. Objectives This paper summarizes the existing research on the practice of PCC in the MENA region and uses this analysis to consider the key elements of a PCC definition based on MENA cultural contexts. Methods Five electronic databases were searched (EMBASE, Cochrane, Medline, CINAHL and Scopus) using the search terms: patient OR person OR client OR consumer AND centered OR centred AND care. The MENA countries included were Bahrain, Iran, Iraq, Jordan, Kuwait, Lebanon, Oman, Palestine, Israel, Qatar, Saudi Arabia, Syria, United Arab Emirates, Yemen, Algeria, Egypt, Libya, Morocco, Tunisia, Djibouti, Pakistan, Sudan, and Turkey. Identified papers were imported to Covidence where they were independently reviewed against the inclusion criteria by two authors. The following data were extracted for each paper: author, year, location (i.e., country), objectives, methodology, study population, and results as they related to patient centred care. Result The electronic search identified 3582 potentially relevant studies. Fifty articles met the inclusion criteria. Across all papers five themes were identified: 1) patient centered care principles; 2) patient and physician perceptions of PCC; 3) facilitators of PCC; 4) implementation and impact of PCC; and 5) barriers to PCC. Conclusion The preliminary findings suggest that the concept of PCC is practiced and supported to a limited extent in the MENA region, and that the implementation of PCC might be impacted by the cultural contexts of the region. Our review therefore highlights the importance of establishing patient-centered care definitions that clearly incorporate cultural practices in the MENA region. The elements and impact of culture in the MENA region should be investigated in future research.